2022
DOI: 10.1002/htj.22698
|View full text |Cite
|
Sign up to set email alerts
|

Maximization of heat transfer density from radially finned tubes in cross‐flow using the constructal design method

Abstract: The maximization of volumetric heat transfer density from radially finned tubes in cross‐flow is investigated in this study based on the constructal design method. A row of radially finned tubes is placed in cross‐air flow. The tubes and the radial fins are heated at uniform temperatures and cooled by the air cross‐flow. The cross‐air flow is generated by a finite pressure difference. Two dimensionless pressure differences (Bejan number) are considered (Be = 103 and Be = 105). The objective function, the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…The results showed that the triangular fin was better than the rectangular fin for ( Re < 200) at Rayleigh number ( Ra = 10 5 ). Mustafa et al 9 used the constructal design method to predict the heat transfer density from radially‐finned tubes in forced convection with constant pressure drop. The finned tubes are designed with five degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the triangular fin was better than the rectangular fin for ( Re < 200) at Rayleigh number ( Ra = 10 5 ). Mustafa et al 9 used the constructal design method to predict the heat transfer density from radially‐finned tubes in forced convection with constant pressure drop. The finned tubes are designed with five degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the thermal conductance increased as the small fins were placed between the large‐scale fins. Mustafa et al 5 studied the forced convection from a set of radially finned tubes using a constructal design approach. They showed that the heat transfer was maximized for each radial fin number.…”
Section: Introductionmentioning
confidence: 99%
“…2024;53:1168-1189. wileyonlinelibrary.com/journal/htj the fin eccentricity (ε = 0.25). The increase in the double maximized heat density when the fin eccentricity (ε = 0.25) is 7.65% for Be = 10 3 , and it is 12% for Be = 10 5 .…”
mentioning
confidence: 96%
See 1 more Smart Citation